High-capacity sodium manganese pyrophosphate positive electrode material capable of regulating and controlling content of P2O7 as well as preparation method and application of high-capacity sodium manganese pyrophosphate positive electrode material

Through the preparation method of sodium manganese pyrophosphate positive electrode material that regulates the P2O7 content, the problem of poor electronic conductivity of sodium manganese pyrophosphate material is solved, high specific capacity and structural stability are achieved, production costs are reduced, and it is suitable for sodium ion batteries.

CN120300181APending Publication Date: 2025-07-11XIAN TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510195578.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-07-11

AI Technical Summary

Technical Problem

The existing polyanionic sodium manganese pyrophosphate materials have poor electronic conductivity and low kinetic performance, which leads to their specific capacity being much lower than the theoretical value, limiting their application in sodium ion batteries.

Method used

By regulating the P2O7 content, Na2Mn(P2O7)(1-X) material was prepared by regulating the P2O7 content and using one-step spray drying method combined with heat treatment, with X of 0.02-0.06, forming a high-capacity sodium manganese pyrophosphate positive electrode material, simplifying the preparation process and improving the dispersion and uniformity of the material.

Benefits of technology

实现了高比容量162.4mAh/g的焦磷酸锰钠正极材料,提升了电子导电性和结构稳定性,降低了生产成本,符合绿色化学要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120300181A_ABST
    Figure CN120300181A_ABST
Patent Text Reader

Abstract

The invention relates to a high-capacity sodium manganese pyrophosphate positive electrode material capable of regulating and controlling the content of P2O7 and a preparation method and application thereof.The preparation method comprises the steps that sodium acetate trihydrate, manganese acetate tetrahydrate and ammonium dihydrogen phosphate are added into deionized water, citric acid monohydrate is added, the mixture is stirred to be uniform, a precursor solution is obtained, spray drying is conducted, and a sodium manganese pyrophosphate precursor material capable of regulating and controlling the content of P2O7 is obtained; and placing the precursor material in an alumina crucible, placing the alumina crucible in a box-type furnace or a tube furnace, and carrying out heat treatment in an argon atmosphere to obtain the sodium manganese pyrophosphate material for regulating and controlling the content of P2O7. The preparation method has the advantages that the electronic structure of the material is changed by regulating and controlling the content of P2O7 polyanion groups and reducing the content of the P2O7 groups in the sodium manganese pyrophosphate structure, the thermodynamic induction effect is reduced, the oxidation-reduction potential is reduced, the multi-electron transfer reaction is promoted, and the high specific capacity is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cathode material for a sodium-ion battery, a preparation method and an application thereof, and particularly relates to a high-capacity sodium pyrophosphate manganese cathode material for a sodium-ion battery with regulated P2O7 content, and a preparation method and an application thereof. Background Art

[0002] Sodium-ion batteries and lithium-ion batteries both belong to monovalent batteries. Moreover, sodium resources are rich in reserves and low in cost, so they are regarded as potential substitutes for lithium-ion batteries. Although the energy density of current sodium-ion batteries is lower than that of lithium-ion batteries, their cost advantage is significant. They have been widely used in fields with low requirements for energy density but large application demands, such as small and medium-sized electric vehicles in the city, short-distance transportation vehicles outside the city, and large-scale energy storage system fields.

[0003] The polyanionic sodium pyrophosphate manganese (Na2MnP2O7) material can utilize the variable valence characteristics of transition metal Mn ions to achieve the deintercalation and intercalation of two sodium ions, thereby generating a high specific capacity and energy density. Its theoretical capacity is as high as 195 mAh / g. Moreover, due to the strong induction of the P2O7 polyanion group, this cathode material has a relatively high working potential. Only the Mn 3+ / Mn 2+ redox electron transfer reaction has a high voltage of about 3.8 V (vs. Na + / Na). In terms of structural stability, the robust three-dimensional framework can significantly reduce the structural changes during the charge and discharge sodium ion deintercalation / intercalation process. Moreover, the strong P-O covalent bond energy in the structure can effectively inhibit the precipitation of oxygen, having good safety. In addition, the elements used (Na, Mn, P) are rich in reserves, low in cost and environmentally friendly. Therefore, the Na2MnP2O7 material has the advantages of high theoretical capacity, high working potential, good structural stability, high safety and low cost, and has the potential for large-scale energy storage applications as an electrode material for sodium-ion batteries. However, the redox reaction of the polyanionic sodium pyrophosphate manganese (Na2MnP2O7) material is restricted by its high thermodynamic stability and poor kinetics. Na2MnP2O7 has a large band gap and is located in the insulating region (5 eV), resulting in poor electron conductivity; although it has a three-dimensional sodium ion diffusion path, the diffusion coefficient is low. Due to the induction of the polyanion group in the structure, its redox reaction potential is relatively high, restricting the occurrence of some redox reactions. These three factors greatly affect the electrochemical performance of the material, especially the specific capacity. The actually reported specific capacity of the sodium pyrophosphate manganese (Na2MnP2O7) material as a cathode material is much lower than its theoretical specific capacity of 195 mAh / g.

[0004] At present, attempts have been made to improve the electronic conductivity of sodium manganese pyrophosphate cathode materials by means such as doping and carbon coating. For example, after the research team of Professor Jiao Lifang from Nankai University improved its electronic conductivity by compounding graphene, the discharge specific capacity was only 93 mAh / g (0.1C) (Energy Storage Mater., 16 (2019) 383–390); CN 201711118657.8 discloses "a composite cathode material of sodium manganese pyrophosphate / carbon and its preparation and application", and this material is a mixed material of sodium manganese pyrophosphate Na 6.24 Mn 4.88 (P2O7)4 and carbon to improve its electronic conductivity, but the initial discharge specific capacity is only 96.8 mAh / g. It can be seen from this that although the electronic conductivity and ionic conductivity have been greatly improved by means such as doping and carbon coating, the specific capacity is still relatively low. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a high-capacity sodium manganese pyrophosphate cathode material with regulated P2O7 content and its preparation method.

[0006] The technical solution of the present invention is as follows: A high-capacity sodium manganese pyrophosphate cathode material, the chemical formula thereof is Na2Mn(P2O7) (1-X) , where X is 0.02 to 0.06.

[0007] Further, the X is 0.02.

[0008] A preparation method of a high-capacity sodium manganese pyrophosphate cathode material, comprising the following steps: (1) Prepare a precursor solution Sodium acetate trihydrate, manganese acetate tetrahydrate and ammonium dihydrogen phosphate are added to deionized water according to a molar ratio of 2.1: (0.98 to 0.94) to prepare a mixed solution, and then citric acid monohydrate is added according to a molar ratio of 1:1 to manganese acetate tetrahydrate, and stirred evenly to obtain a precursor solution; (2) Prepare a precursor material The precursor solution is sent to a spray dryer by a peristaltic pump. The temperature at the inlet of the spray dryer is 200°C to 300°C, the temperature at the outlet is 100°C, and spray drying is carried out under a pressure of 2 Bar to obtain a sodium manganese pyrophosphate precursor material with regulated P2O7 content; (3) Preparation of sodium manganese pyrophosphate with regulated P2O7 content The precursor material is placed in an alumina crucible, and the alumina crucible is placed in a box furnace or a tube furnace. Heat treatment is carried out at 600°C for 2 h to 3 h under an argon atmosphere to obtain a sodium manganese pyrophosphate material with regulated P2O7 content.

[0009] Further, the molar ratio of sodium acetate trihydrate, manganese acetate tetrahydrate, and ammonium dihydrogen phosphate - boric acid is 2.1:1:0.98.

[0010] Further, the molar volume ratio of manganese acetate tetrahydrate to deionized water is 0.15 mol·L -1 .

[0011] Further, the molar volume ratio of citric acid monohydrate to deionized water is 0.15 mol·L -1 .

[0012] Further, the stirring time in step (1) is 2 h.

[0013] Further, the inlet temperature of the spray dryer is 200 °C.

[0014] Further, the heating rate of the heat treatment is 3 °C·min -1 , and the heat treatment time is 3 h.

[0015] An application of the above - mentioned high - capacity sodium manganese pyrophosphate cathode material in a sodium - ion battery cathode material.

[0016] Advantages of the present invention: (1) By regulating the content of the P2O7 polyanion group, reducing the content of the P2O7 group in the sodium manganese pyrophosphate structure changes the electronic structure of the material, which is beneficial to reducing the thermodynamic induction effect, lowering the redox potential, and then promoting the realization of a multi - electron transfer reaction, achieving a high specific capacity. The actual specific capacity is as high as 162.4 mAh / g.

[0017] (2) By using a one - step spray - drying method combined with heat treatment, the rapid and uniform reaction of metal salts, phosphates, and sodium ions is achieved, forming a composite of sodium manganese pyrophosphate powder with regulated P2O7 content and in - situ coated conductive carbon. This method not only simplifies the preparation process but also improves the dispersibility and uniformity of the material.

[0018] (3) Although the content of P2O7 is reduced, through reasonable structural design, the present invention still maintains the structural stability of the material. At the same time, due to the strong induction effect of the P - O covalent bond, the material can effectively inhibit the oxygen evolution during charge - discharge, improving the safety of the battery.

[0019] (4) The elements (Na, Mn, P) used in the present invention are all raw materials with rich reserves and low costs, and no complex doping or coating processes are required during the preparation process, further reducing the production cost and improving the market competitiveness.

[0020] (5) The raw materials used are all environmentally friendly materials, and no harmful substances are emitted during the preparation process, meeting the concepts of green chemistry and sustainable development. Description of the Drawings

[0021] Figure 1 XRD patterns of sodium manganese pyrophosphate materials prepared in Comparative Example 1, Example 1, and Comparative Example 2 of the present invention; Figure 2 XPS patterns of sodium manganese pyrophosphate materials prepared in the corresponding comparative examples, Example 1, and Comparative Example 2 of the present invention; Figure 3 Raman patterns of sodium manganese pyrophosphate materials prepared in the corresponding comparative examples, Example 1, and Comparative Example 2 of the present invention; Figure 4 SEM patterns of sodium manganese pyrophosphate materials prepared in the corresponding comparative examples, Example 1, and Comparative Example 2 of the present invention; Figure 5 Charge-discharge curves of sodium manganese pyrophosphate materials prepared in Comparative Example 1, Comparative Example 2, and Examples 1-3 of the present invention. Detailed implementation manners

[0022] Example 1 (1) Prepare the precursor solution According to sodium manganese pyrophosphate being Na2Mn(P2O7) 0.98 Weigh the ingredients according to the stoichiometric ratio, with sodium in excess by 5% to compensate for sodium loss during high-temperature sintering. Weigh 42.8652 g of sodium acetate trihydrate, 36.7635 g of manganese acetate tetrahydrate, and 33.8188 g of ammonium dihydrogen phosphate, dissolve them in 1 L of deionized water, and add 31.52 g of citric acid monohydrate; mechanically stir at room temperature for 2 hours to obtain the precursor solution; (2) Prepare the precursor material Use a peristaltic pump to send the precursor solution to a spray dryer. The inlet temperature of the spray dryer is 200 °C and the outlet temperature is 100 °C. Spray dry at a pressure of 2 Bar to obtain the precursor material; (3) Preparation of sodium manganese pyrophosphate with regulated P2O7 content Place the precursor material in an alumina crucible with a diameter of 50 mm and a length of 100 mm. Place the alumina crucible in a tubular furnace, fill with argon as the protective gas, and heat at a heating rate of 3 °C·min -1 Heat up and perform heat treatment at 600 °C for 3 h in an argon atmosphere to obtain the sodium manganese pyrophosphate cathode material.

[0023] Example 2 (1) Prepare the precursor solution According to sodium manganese pyrophosphate being Na2Mn(P2O7) 0.96Ingredients are prepared according to the stoichiometric ratio, with sodium in excess by 5% to compensate for sodium loss during high-temperature sintering. Weigh 42.8652 g of sodium acetate trihydrate, 36.7635 g of manganese acetate tetrahydrate, and 33.1286 g of ammonium dihydrogen phosphate, dissolve them in 1 L of deionized water, and add 31.52 g of citric acid monohydrate, with sodium in excess by 5% to compensate for sodium loss during high-temperature sintering; mechanically stir for 2 hours at room temperature to obtain a precursor solution; (2) Preparation of precursor material Use a peristaltic pump to send the precursor solution to a spray dryer. The inlet temperature of the spray dryer is 200 °C and the outlet temperature is 100 °C. Spray dry at a pressure of 2 Bar to obtain a precursor material; (3) Preparation of sodium manganese pyrophosphate with regulated P2O7 content Place the precursor material in an alumina crucible with a diameter of 50 mm and a length of 100 mm. Place the alumina crucible in a tube furnace, fill it with argon as a protective gas, and heat it at a heating rate of 3 °C·min -1 Heat up, and heat-treat for 3 h at 600 °C in an argon atmosphere to obtain a sodium manganese pyrophosphate cathode material.

[0024] Example 3 (1) Preparation of precursor solution According to sodium manganese pyrophosphate being Na2Mn(P2O7) 0.94 Ingredients are prepared according to the stoichiometric ratio, with sodium in excess by 5% to compensate for sodium loss during high-temperature sintering. Weigh 42.8652 g of sodium acetate trihydrate, 36.7635 g of manganese acetate tetrahydrate, and 32.4384 g of ammonium dihydrogen phosphate, dissolve them in 1 L of deionized water, and add 31.52 g of citric acid monohydrate, with sodium in excess by 5% to compensate for sodium loss during high-temperature sintering; mechanically stir for 2 hours at room temperature to obtain a precursor solution; (2) Preparation of precursor material Use a peristaltic pump to send the precursor solution to a spray dryer. The inlet temperature of the spray dryer is 200 °C and the outlet temperature is 100 °C. Spray dry at a pressure of 2 Bar to obtain a precursor material; (3) Preparation of sodium manganese pyrophosphate with regulated P2O7 content Place the precursor material in an alumina crucible with a diameter of 50 mm and a length of 100 mm. Place the alumina crucible in a tube furnace, fill it with argon as a protective gas, and heat it at a heating rate of 3 °C·min -1 Heat up, and heat-treat for 3 h at 600 °C in an argon atmosphere to obtain a sodium manganese pyrophosphate cathode material.

[0025] Comparative Example 1 (1) Preparation of precursor solution According to sodium manganese pyrophosphate is Na2Mn(P2O7) 0.92 Weigh the ingredients according to the stoichiometric ratio, with sodium in excess by 5% to compensate for sodium loss during high-temperature sintering. Weigh 42.8652 g of sodium acetate trihydrate, 36.7635 g of manganese acetate tetrahydrate, and 31.748 g of ammonium dihydrogen phosphate, dissolve them in 1 L of deionized water, and add 31.52 g of citric acid monohydrate; mechanically stir for 2 hours at room temperature to obtain a precursor solution; (2) Preparation of precursor material Use a peristaltic pump to send the precursor solution to a spray dryer. The inlet temperature of the spray dryer is 200 °C and the outlet temperature is 100 °C. Spray dry under a pressure of 2 Bar to obtain the precursor material; (3) Preparation of sodium manganese pyrophosphate with regulated P2O7 content Place the precursor material in an alumina crucible with a diameter of 50 mm and a length of 100 mm. Place the alumina crucible in a tube furnace, fill with argon as a protective gas, and heat at a heating rate of 3 °C·min -1 Heat up, and heat-treat at 600 °C for 3 h under an argon atmosphere to obtain the sodium manganese pyrophosphate cathode material.

[0026] Comparative Example 2 (1) Preparation of precursor solution Weigh the ingredients according to the stoichiometric ratio of sodium manganese pyrophosphate as Na2MnP2O7, with sodium in excess by 5% to compensate for sodium loss during high-temperature sintering. Weigh 42.8652 g of sodium acetate trihydrate, 36.7635 g of manganese acetate tetrahydrate, and 34.5090 g of ammonium dihydrogen phosphate, dissolve them in 1 L of deionized water, and add 31.52 g of citric acid monohydrate; mechanically stir for 2 hours at room temperature to obtain a precursor solution; (2) Preparation of precursor material Use a peristaltic pump to send the precursor solution to a spray dryer. The inlet temperature of the spray dryer is 200 °C and the outlet temperature is 100 °C. Spray dry under a pressure of 2 Bar to obtain the precursor material; (3) Preparation of sodium manganese pyrophosphate Place the precursor material in an alumina crucible with a diameter of 50 mm and a length of 100 mm. Place the alumina crucible in a tube furnace, fill with argon as a protective gas, and heat at a heating rate of 3 °C·min -1 Heat up, and heat-treat at 600 °C for 3 h under an argon atmosphere to obtain the sodium manganese pyrophosphate cathode material.

[0027] I. XRD tests of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention Perform XRD tests on the sodium manganese pyrophosphate cathode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. The test results are as followsFigure 1 As shown in Figure 1 It can be seen that the positions and relative intensities of the X-ray diffraction peaks are consistent with the standard card 019-089-8448 of Na2MnP2O7. It is proved that the high-purity Na2MnP2O7 material with good crystallinity in the triclinic P-1 space group has been successfully prepared. It should be noted that in Comparative Example 1, when the content of P2O7 decreases significantly, some impurity phases such as NaMnP2O7 and Na4P2O7 appear, which seriously affects the specific capacity of the material.

[0028] II. XPS Tests of Example 1, Comparative Example 1, and Comparative Example 2 of the Present Invention XPS tests were carried out on the sodium manganese pyrophosphate cathode materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. The test results are as Figure 2 shown in Figure 2 It can be seen that the XPS signal peak of P element was detected in the sodium manganese pyrophosphate cathode material provided in this example. The P2p binding energy of the sodium manganese pyrophosphate cathode material with regulated P2O7 content shifted towards the lower binding energy direction, indicating that the electronic structure changed, the electronic environment of the P atom became more electron-deficient, that is, the electron cloud density decreased, resulting in a decrease in the binding energy, weakening the inductive effect of the adjacent polyanion group, promoting the electron transfer reaction, and being beneficial to the improvement of the specific capacity.

[0029] III. Raman Tests of Example 1, Comparative Example 1, and Comparative Example 2 of the Present Invention Raman tests were carried out on the sodium manganese pyrophosphate cathode materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention to observe the Raman peaks of the conductive carbon in the sodium manganese pyrophosphate cathode material. The test results are as Figure 3 shown in Figure 3 It can be seen that the in-situ composite carbon of the sodium manganese pyrophosphate cathode material with reduced P2O7 content prepared in Example 1 of the present invention has a higher I D / I G than those of Comparative Example 1 and Comparative Example 2, with more defects and easier electron conduction, thus promoting the electron transfer in the electrochemical process of the cathode material and being beneficial to the improvement of the specific capacity.

[0030] IV. SEM Tests of Example 1, Comparative Example 1, and Comparative Example 2 of the Present Invention SEM tests were carried out on the sodium manganese pyrophosphate cathode materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention to observe the morphology and size of the sodium manganese pyrophosphate cathode material. The test results are as Figure 4 shown in Figure 4It can be seen that the sodium pyrophosphate manganese cathode material prepared in Example 1 of the present invention and Comparative Example 2 has a smooth surface and uniform size, about 50 nm. However, when the content of P2O7 in Comparative Example 2 decreases significantly, the particle size grows significantly, about 100 - 200 nm. According to the inverse relationship between the sodium ion diffusion coefficient and the particle size, this will lead to a decrease in the sodium ion diffusion kinetics, which is not conducive to the performance of the specific capacity.

[0031] V. Electrochemical performance test of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention (I) Assembly of CR2025 stainless steel button-type sodium ion battery (1) Preparation of the positive electrode sheet Weigh the sodium pyrophosphate manganese cathode material (prepared in Example 1 - 3, Comparative Example 1 or Comparative Example 2 of the present invention), Super P and CMC according to the mass ratio of 70:20:10 and place them in a ball milling jar (where CMC is added in the form of an aqueous CMC solution). The mass concentration of the aqueous CMC solution is 1.2 wt%. Add tungsten carbide ball milling beads. The mass ratio of balls to materials in the ball milling jar is 20:1. After ball milling for 6 h, coat it on the aluminum foil with a 0.1 μm doctor blade, place it in a vacuum drying oven at 110 °C for drying for 20 h, cut it into a positive electrode sheet with a diameter of 10 mm, and then transfer the cut positive electrode sheet to a vacuum oven at 115 °C for drying for 10 h to obtain the positive electrode sheet; (2) Assembly of CR2025 stainless steel button-type sodium ion battery Use a sodium metal sheet as the negative electrode, drop 200 μL of commercial electrolyte, and complete the assembly of the CR2025 stainless steel button battery in a glove box filled with argon and with a water content lower than 0.01 ppm. After standing at 45 °C for 40 h, test its charge-discharge performance.

[0032] (II) Electrochemical performance test of CR2025 stainless steel button-type sodium ion battery Adopt the constant current charge-discharge method to test the cycle performance of the batteries prepared in Comparative Examples 1 and 2 and Examples 1 - 3. The test temperature is 25 °C, the voltage window is 1.5 - 4.55 V, and the test current densities are 0.02C respectively, where 1C = 200 mA / g.

[0033] As Figure 5 shown, slightly reducing the content of P2O7 significantly increases the specific capacity of the sodium pyrophosphate manganese cathode material. The sodium ion battery prepared from the sodium pyrophosphate manganese Na2Mn(P2O7) 0.98 positive electrode material in Example 1 of the present invention has an initial discharge specific capacity of 162.4 mAh / g at a current density of 0.02C, which is significantly higher than the sodium storage capacity of the sodium pyrophosphate manganese cathode material in Comparative Example 2. When the content of P2O7 decreases too much, the particle size increases and is accompanied by the generation of impurity phases. Na2Mn(P2O7)1-x, (x = 0.08) The specific capacity of the material is lower than that of Na2Mn(P2O7). 1.0 Lower.

[0034] In summary, for the high-capacity sodium manganese pyrophosphate cathode material of the present invention, by reducing the highly electronegative phosphorus polyanion group, changing the thermodynamic induction effect of the material, and promoting the multi-electron transfer reaction, a high specific capacity is achieved. This preparation method has the advantages of low cost, simple operation, and easy industrial application.

[0035] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A high-capacity sodium manganous pyrophosphate cathode material, characterized in that: Its chemical formula is Na2Mn(P2O7) (1-X) , where X = 0.02 to 0.

06.

2. The high-capacity sodium pyrophosphate manganese cathode material according to claim 1, characterized in that: The X is 0.

02.

3. A preparation method of the high-capacity sodium manganese pyrophosphate cathode material as described in claim 1, characterized in that: It includes the following steps: (1) Prepare a precursor solution Sodium acetate trihydrate, manganese acetate tetrahydrate and ammonium dihydrogen phosphate are added to deionized water according to a molar ratio of 2.1:(0.98 - 0.94) to prepare a mixed solution, and then citric acid monohydrate is added according to a molar ratio of 1:1 to manganese acetate tetrahydrate, and stirred evenly to obtain a precursor solution; (2) Prepare a precursor material The precursor solution is sent to a spray dryer by a peristaltic pump. The temperature at the inlet of the spray dryer is 200°C - 300°C and the outlet temperature is 100°C. Spray drying is carried out under a pressure of 2 Bar to obtain a sodium manganese pyrophosphate precursor material with regulated P2O7 content; (3) Preparation of sodium manganese pyrophosphate with regulated P2O7 content The precursor material is placed in an alumina crucible, and the alumina crucible is placed in a box furnace or a tube furnace. Heat treatment is carried out at 600°C for 2 h - 3 h under an argon atmosphere to obtain a sodium manganese pyrophosphate material with regulated P2O7 content.

4. The preparation method of the high-capacity sodium manganous pyrophosphate cathode material according to claim 3, characterized in that: The molar ratio of the sodium acetate trihydrate, manganese acetate tetrahydrate, and ammonium dihydrogen phosphate boric acid is 2.1:1:0.

98.

5. The preparation method of the high-capacity sodium manganous pyrophosphate cathode material according to claim 3, characterized in that: The molar volume ratio of the manganese acetate tetrahydrate to deionized water is 0.15 mol·L -1 .

6. The preparation method of the high-capacity sodium manganous pyrophosphate cathode material according to claim 3, characterized in that: The molar volume ratio of the citric acid monohydrate to deionized water is 0.15 mol·L -1 .

7. The preparation method of the high-capacity sodium manganous pyrophosphate cathode material according to claim 3, characterized in that: The stirring time in step (1) is 2 h.

8. The preparation method of the high-capacity sodium manganous pyrophosphate cathode material according to claim 3, characterized in that: The inlet temperature of the spray dryer is 200°C.

9. The preparation method of the high-capacity sodium manganous pyrophosphate cathode material according to claim 3, characterized in that: The heating rate of heat treatment is 3 °C·min -1 , and the heat treatment time is 3 h.

10. Application of the high-capacity sodium manganese pyrophosphate cathode material as described in claim 1 in a sodium-ion battery cathode material.

Citation Information

Patent Citations

  • A composite cathode material of sodium manganese pyrophosphate / carbon and its preparation and application

    CN107978738B